Lucille Wright: capstone - Wright, Lucille, artist (Colorado State University. Libraries, 2022)
The artist's statement: We plant seeds in soil made from decomposed corpses and wonder why the flower looks familiar. I work in a combination of traditional 2D animation, stop-motion, rotoscoping, scanned-image animation, and collected footage. My pieces combine techniques and imagery. I find inspiration for my pieces by looking backwards. What is happening now has happened before. What is happening now is a culmination of the efforts of those who came before us. This fight is an old one. And the fight before it was even older. History has proven to us again and again that we are fickle creatures, set on repeating ourselves. I try to express this in my pieces. The iterative nature of our problems. They evolve. We make progress. But we fall into the same worn-down ruts.I am interested in how history repeats itself. How our human race manages to run itself in a circle. Animation is to bring life. It comes from the latin root "anima," meaning life and breath. While I believe my art is alive, its purpose is not to birth something new. My artwork has a much more fungal quality. It lingers between life and death. It secretes itself into the contemporary and takes it over with something fouler. Something old. Digesting in order to create.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: electronic art